How Grab Becomes One of the Greatest Start-ups in South-East Asia - Kee, Daisy Mui Hung; Mohd Rusdi, Syahidatul A’fifah; Mokhtar, Siti Sarah; Muhamad Ridzuan, Siti Aisyah; Amni Abdullah, Siti Aishah (International Journal of Tourism and Hospitality in Asia Pasific, 2021)
Headquartered in Singapore, Grab is a multinational ride-hailing company in Southeast Asia. Grab's service has been classified by the Department of Transportation and Communications (DOTC) under what they defined as Transportation Network Company (TNC). They use cloud-based mobile technology to provide ride-hailing and logistics, food delivery, paying bills, and others. The study aims to analyze how Grab becomes one of the greatest start-ups in South-East Asia. This study began with gathering information about Grab's factors in start-ups while operating towards their mission. Grab's mission is to solve people's problems to drive Southeast Asia forward and deliver a positive social impact for hundreds of millions of people. Grab has served helpful services for users as they had mastered the super apps.